Certeza do direito e a previsibilidade das decisões judiciais na reforma do Processo Civil brasileiro: aspectos sistêmicos e históricos dos mecanismos de uniformização de jurisprudência e aceleração do processo - Zapater, Tiago Cardoso Vaitekunas (2014)
This study proposes to critically analyze the mechanisms implemented as a result of reforms in the Brazilian civil procedure in the last two decades, that aims to standardize court decisions and expedite procedure. The study sustains that , given the conditions under which the Law operates in contemporary society, these mechanisms are unusable to provide court decisions with predictability nor certainty, because these mechanisms tends to become, themselves, a source of uncertainty and unpredictability. Mechanisms of court decisions standardization, such as the Brazilian binding precedent ( súmula vinculante ), depends upon proceedings and legal requirements that undermine the autonomy of the Legal System s operational code, which exposes the system to attacks from the code of other systems, such as Economy and Politic. Mechanisms to expedite proceedings, such as the Court s monocratic ruling by the reporting Justice, by their turn, engender losses in the system s capacity to legitimate judicial decisions by means of the legal proceeding, which also generates uncertainty regarding the social adequacy of the judicial decision. The present work uses Niklas Luhmann s system theory to describe the conditions under which the Law operates in the society, as well as the interrelated Guilherme Leite Gonçalves s thesis, also based upon system theory, to whom problems related to certainty of Law arises out of modern society s semantic inadequacy to describe a society that no longer can count on the old metaphysic certainty centers of the pre-modern societies. The application of the system theory to the Brazilian s Judiciary is based upon Celso Fernandes Campilongo and Orlando Villas Bôas Filho s theoretical approaches, according to which Brazilian Law is a case of an autopoietic system, to which the system theory may be applied, and that suffers with the overload of burdens arising from its environment and hardship to protect the system s center (the Courts) from such burden, which jeopardize the system s autonomy. With this instrumental, the study analyzes the history of the control mechanisms of Court s interpretation of the Law, upon which standardization of Court decisions is based, as well as its main theoretical references, such as common Law s stare decisis et non quite movere and the recent jurisprudence on equality on the application of Law and the right to a expedite trial